Thermo-mechanical response of rigid plastic laminates for greenhouse covering - Silvana Fuina; Giuseppe C. Marano; Giuseppe Puglisi; Domenico De Tommasi; Giacomo Scarascia-Mugnozza (Journal of Agricultural Engineering, 2016)
Innovation in the field of protected crops represents an argument of great applied and theoretical research attention due to constantly evolving technologies and automation for higher quality flower and vegetable production and to the corresponding environmental and economic impact. The aim of this paper is to provide an analysis of some thermomechanical properties of rigid polymeric laminates for greenhouses claddings, including innovative tests such as the thermographic ones. Four types of laminates have been analysed: two polycarbonates, a polymethylmethacrylate and a polyethylene terephthalate (PET). The tests gave interesting results on different important properties, such as radiometric properties, limit stresses, strains and ductility. Moreover, a direct comparison of infrared images and force elongation curves gave important information on the relation of the (localised or homogeneous) damage evolution, with both an applicative and theoretical implication. Finally, even if to the authors knowledge at present there are no examples of using PET for covering greenhouses, the results of this paper indicates the thermomechanical and radiometric characteristics of this material make it interesting for agricultural applications.